High-temperature-resistant welding slag-resistant cable sheath material
By using the formulation of TPU, modified montmorillonite and crosslinking resin in the welding slag-proof cable sheath material, an interpenetrating crosslinking network is formed, which solves the problem of easy deformation and poor robustness of the sheath material at high temperatures, and realizes the Good high temperature resistance and welding slag spot resistance.
Patent Information
- Application Number
- CN202411617852.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing welding slag-proof cable sheath material is prone to deform at high temperatures, and the temperature of the welding slag spot is extremely high, resulting in scalding of the sheath material surface and poor stability of TPU resins.
80-100 parts of TPU, 16-32 parts of modified montmorillonite, 18-35 parts of crosslinking resin, 0.1-1.5 parts of processing auxiliary agent, 2-6 parts of crosslinking agent, and 0.1-0.5 parts of reactive catalyst. Formulation, through the hyperbranched chain structure of the crosslinking resin and the filler action of modified montmorillonite, an interpenetrating crosslinking network is formed to improve the material's high temperature resistance and hardness.
The sheath material is not easy to deform at high temperatures, can resist the temperature of welding slag spots, and does not melt on the surface, solving the problems of poor robustness and easy deformation of TPU resins, and at the same time improving the high-temperature oxidation resistance of the material.
Smart Images

Figure BDA0005132724410000031 
Figure BDA0005132724410000032 
Figure BDA0005132724410000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sheath material preparation, and in particular relates to a high temperature resistant and welding slag proof cable sheath material. Background Art
[0002] The raw materials of existing sheath materials include polyvinyl chloride (PVC) resins, polyethylene (PE) resins, polyurethane (PUR) resins, thermoplastic elastomer (TPE or TPR) resins, thermoplastic polyurethane (TPU) resins and other special types. All of the above sheath materials have their own advantages and disadvantages. Among them, PVC sheath materials contain halogens, and their combustion is prone to produce hydrogen halide fumes, and hydrogen halide fumes damage the ecological environment. PE sheath materials are not resistant to high temperatures and are prone to aging under the sun, but they have low production costs and are environmentally friendly. PUR sheath materials have good oil resistance, toughness, wear resistance, cold resistance, water resistance, aging resistance and other properties, but the production cost is high. TPE / TPR sheath materials also have good chemical resistance and oil resistance, as well as excellent flexibility and wear resistance, but poor high temperature resistance and poor firmness. TPU sheath materials have excellent characteristics of high wear resistance, high tension, high tensile force, strong toughness and aging resistance, but poor firmness and easy deformation. Generally, PVC, PUR, TPU or special raw materials with good temperature resistance are used for anti-welding slag cable sheath materials. However, based on environmental protection and production cost, TPU resin is selected as the raw material of anti-welding slag cable sheath materials in the present invention. However, due to the extremely high temperature of the welding slag point (above 200°C), in order to prevent the welding slag point from causing burns to the surface of the sheath material, the TPU sheath material needs to be modified to resist high temperature. At the same time, it is also necessary to overcome the shortcomings of poor firmness and easy deformation of TPU resin. Summary of the invention
[0003] In view of the above-mentioned problems, the present invention provides a high temperature resistant and welding slag resistant cable sheath material.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A high temperature resistant and anti-welding slag cable sheath material, comprising the following raw materials in parts by weight: 80-100 parts of TPU, 16-32 parts of modified montmorillonite, 18-35 parts of cross-linked resin, 0.1-1.5 parts of processing auxiliary agent, 2-6 parts of auxiliary cross-linking agent, and 0.1-0.5 parts of reaction catalyst;
[0006] The cross-linking resin is prepared by mixing and reacting hexamethylene diisocyanate trimer and alcohol hydroxyl double-terminated silicone oil in a molar ratio of 1-1.5:1 in a first organic solvent and in the presence of an organic tin catalyst.
[0007] Furthermore, the alcohol hydroxyl double-terminated silicone oil has an average relative molecular weight of 1500-2000 and a viscosity of 25°C cts 50-100.
[0008] Furthermore, the reaction temperature of the hexamethylene diisocyanate trimer and the alcohol hydroxyl di-terminated silicone oil is 50-70° C., and the reaction time is 4-8 hours.
[0009] Furthermore, the first organic solvent is one of acetone, tetrahydrofuran, benzene and toluene.
[0010] Preferably, the cross-linked resin is prepared by the following steps:
[0011] After uniformly mixing hexamethylene diisocyanate trimer, alcohol hydroxyl di-terminated silicone oil and acetone, heat to 50-70°C under nitrogen protection, add organic tin catalyst while stirring, continue to keep warm and stir the reaction time for 4-8h, stop the reaction, rotary evaporate, wash with water, and dry to obtain a cross-linked resin.
[0012] Furthermore, the preparation reaction of the modified montmorillonite comprises:
[0013] After mixing the sodium-based montmorillonite solution and the solution containing the functional modifier, the pH of the mixed solution is adjusted to 3-5, heated to 70-80°C, stirred for reaction for 6-12 hours, and post-treated to obtain modified montmorillonite;
[0014] Wherein, the sodium-montmorillonite solution is made of sodium-montmorillonite and a first mixed solvent; the solution containing a functional modifier is made of a functional modifier and a first mixed solvent; and the first mixed solvent is formed by mixing water and ethanol.
[0015] Furthermore, the volume ratio of water to ethanol in the first mixed solvent is 1-3:7-9.
[0016] Furthermore, the mass fraction of sodium-montmorillonite in the sodium-montmorillonite solution is 30-50%.
[0017] Furthermore, the mass fraction of the functional modifier in the solution containing the functional modifier is 10-20%.
[0018] Furthermore, the mass ratio of the sodium-montmorillonite to the functional modifier is 10:1-3.
[0019] Furthermore, the functional modifier is prepared by reacting chlorinated hydroxybenzophenone and a polyhydroxylated silane coupling agent in a second organic solvent.
[0020] Preferably, the functional modifier is prepared by reacting chlorinated hydroxybenzophenone and a polyhydroxylated silane coupling agent in a second organic solvent and a first acid coating agent.
[0021] Furthermore, the reaction temperature of the chlorinated hydroxybenzophenone and the polyhydroxylated silane coupling agent is 20-60° C., and the reaction time is 2-5 hours.
[0022] Furthermore, the molar ratio of the chlorinated hydroxybenzophenone to the polyhydroxylated silane coupling agent is 1:1.
[0023] The structural formula of the chlorinated hydroxybenzophenone is shown below.
[0024]
[0025] Furthermore, the molecular structure of the polyhydroxylated silane coupling agent is shown below.
[0026]
[0027] Furthermore, the second organic solvent is one of dichloromethane, tetrahydrofuran, benzene and toluene.
[0028] Furthermore, the polyhydroxylated silane coupling agent is prepared by reacting 3-chloropropyltrimethoxysilane and a polyol in a third organic solvent, and the polyhydroxylated silane coupling agent is a monosubstituted reaction product of 3-chloropropyltrimethoxysilane and a polyol, that is, chlorine in 3-chloropropyltrimethoxysilane replaces one alcoholic hydroxyl group in the polyol.
[0029] Furthermore, the molar ratio of the 3-chloropropyltrimethoxysilane to the polyol is 1:1-1.5.
[0030] Furthermore, the reaction temperature of the 3-chloropropyltrimethoxysilane and the polyol is 60-65° C., and the reaction time is 2-7 hours.
[0031] Preferably, during the reaction of the 3-chloropropyltrimethoxysilane and the polyol in the third organic solvent, an equivalent acid binding agent is added to absorb the hydrogen chloride byproduct generated by the reaction of the 3-chloropropyltrimethoxysilane and the polyol to accelerate the reaction rate.
[0032] Preferably, in the reaction process of the 3-chloropropyltrimethoxysilane and the polyol in the third organic solvent, the 3-chloropropyltrimethoxysilane is added dropwise into a mixed solution of the polyol and the third organic solvent, thereby reducing di-substitution reaction by-products or tri-substitution reaction by-products in the reaction process of the 3-chloropropyltrimethoxysilane and the polyol.
[0033] Preferably, the polyhydroxylated silane coupling agent is prepared by the following steps:
[0034] After mixing the polyol, the second acid binding agent and the third organic solvent, heat to 60-65°C, add 3-chloropropyltrimethoxysilane dropwise, continue to stir and react for 2-7 hours, filter, and recover the organic solvent through rotary evaporation of the filtrate, wash, and dry to obtain a polyhydroxylated silane coupling agent.
[0035] Furthermore, the polyol is one of propylene glycol and pentaerythritol.
[0036] Furthermore, the third organic solvent is one of ethyl acetate, tetrahydrofuran, benzene and toluene.
[0037] Furthermore, the chlorinated hydroxybenzophenone is prepared by reacting chloroacetyl chloride and 2,4-dihydroxybenzophenone in a fourth organic solvent.
[0038] Preferably, the chlorinated hydroxybenzophenone is prepared by reacting chloroacetyl chloride and 2,4-dihydroxybenzophenone in a fourth organic solvent and a third acidifying agent.
[0039] Furthermore, the molar ratio of the chloroacetyl chloride to 2,4-dihydroxybenzophenone is 1-1.5:1.
[0040] Furthermore, the fourth organic solvent is one of dichloromethane, tetrahydrofuran, benzene and toluene.
[0041] Furthermore, the reaction temperature of the chloroacetyl chloride and 2,4-dihydroxybenzophenone is 0-30° C., and the reaction time is 2-7 hours.
[0042] Furthermore, the processing aid is a lubricant.
[0043] Furthermore, the auxiliary cross-linking agent is one or more of 3,3'-dichloro-4,4'-diaminophenylmethane, 3,5-dimethylthiotoluenediamine, diethyltoluenediamine, and 4,4'-methylenebis(2-ethyl)aniline.
[0044] Preferably, the auxiliary cross-linking agent is 3,5-dimethylthiotoluenediamine.
[0045] Furthermore, the reaction catalyst is triethylenediamine.
[0046] Beneficial effects of the present invention:
[0047] The invention provides a high temperature resistant and anti-welding slag cable sheath material. A cross-linking resin is added to TPU, and the cross-linking resin is a silane chain polyurethane with good compatibility with TPU. The cross-linking resin uses a relatively large amount of free isocyanate groups in the hyperbranched chain structure of the cross-linking resin, free amino groups or hydroxyl groups in TPU, and a cross-linking aid. In the subsequent processing, the isocyanate groups react with the hydroxyl groups and amino groups under the action of a catalyst to generate cross-linking, thereby forming an interpenetrating cross-linking network in the composite material finally obtained.
[0048] Secondly, the present invention adds modified montmorillonite to TPU and utilizes the filler function of montmorillonite to eliminate the problem that the TPU system is made softer (making the composite material less durable than the original TPU) due to the introduction of silane chains, thereby improving the hardness of the obtained composite material; and the high temperature resistance of montmorillonite, the high temperature resistance of the silane chain, and the temperature resistance of the interpenetrating cross-linked network form a triple high temperature resistance modification, which synergistically enables the obtained composite material to resist the temperature of the welding slag point without melting on the surface, thereby solving the problems mentioned in the background technology;
[0049] In addition, the modified montmorillonite is modified by a functional modifier, which not only realizes the organic modification of the surface of the montmorillonite and improves its dispersibility in organic matter, but also realizes the purpose of high temperature oxidation resistance modification of the montmorillonite. The introduction of the modified montmorillonite improves the high temperature oxidation resistance of the composite material while improving the firmness of the TPU. DETAILED DESCRIPTION
[0050] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] Preparation of functional modifiers:
[0053] A1. After uniformly mixing 0.1 mol chloroacetyl chloride and 70 mL dichloromethane, 70 mL dichloromethane containing 0.1 mol 2,4-dihydroxybenzophenone and 0.2 mol triethylamine (acting as the third acidifying agent, in excess) was added dropwise to the mixed solution under an ice-water bath. After complete addition, the mixture was slowly heated to room temperature, and the reaction was continued with stirring for 4 h. The mixture was washed with water, separated, the organic layer was taken, rotary evaporated, washed with methanol, the organic layer was taken, concentrated and cooled again, and dried to obtain chlorinated hydroxybenzophenone;
[0054] A2, 0.12 mol glycerol, 0.2 mol aluminum oxide (acting as the second acidifying agent, in excess) and 120 mL ethyl acetate were mixed, heated to 60-65°C, 0.1 mol 3-chloropropyltrimethoxysilane was added dropwise, and after addition, the mixture was stirred and kept warm for 3 hours, filtered, and the filtrate was subjected to rotary evaporation to recover the organic solvent, washed, and dried to obtain a polyhydroxylated silane coupling agent;
[0055] A3. Mix 0.1 mol chlorohydroxybenzophenone, 0.1 mol polyhydroxylated silane coupling agent, 0.15 mol triethylamine (acting as the first acidifying agent, in excess) and 100 mL dichloromethane in an ice-water bath. After mixing, slowly heat to 60°C, stir to react for 2 h, wash with water, separate the liquids, rotary evaporate the organic phase, and dry to obtain a functional modifier.
[0056] Example 2
[0057] Preparation of functional modifiers:
[0058] A1. After 0.15 mol chloroacetyl chloride and 70 mL dichloromethane were mixed evenly, 70 mL dichloromethane containing 0.1 mol 2,4-dihydroxybenzophenone and 0.2 mol triethylamine (acting as the third acidifying agent) was added dropwise to the mixed solution under an ice-water bath. After the addition was complete, the mixture was slowly heated to room temperature, and the reaction was continued with stirring for 7 h. The mixture was washed with water, separated, the organic layer was taken, rotary evaporated, washed with methanol, the organic layer was taken, concentrated and cooled again, and dried to obtain chlorinated hydroxybenzophenone;
[0059] A2, 0.15 mol pentaerythritol, 0.2 mol aluminum oxide (acting as the second acidifying agent) and 120 mL ethyl acetate were mixed, heated to 60-65°C, 0.1 mol 3-chloropropyltrimethoxysilane was added dropwise, and the mixture was stirred and reacted for 7 hours, filtered, and the filtrate was subjected to rotary evaporation to recover the organic solvent, washed, and dried to obtain a polyhydroxylated silane coupling agent;
[0060] A3. Mix 0.1 mol chlorohydroxybenzophenone, 0.1 mol polyhydroxylated silane coupling agent, 0.15 mol triethylamine (acting as the first acidifying agent) and 100 mL dichloromethane in an ice-water bath. After mixing, slowly heat to 40°C, stir and react for 5 hours, wash with water, separate the liquids, rotary evaporate the organic phase, and dry to obtain a functional modifier.
[0061] Example 3
[0062] Preparation of modified montmorillonite:
[0063] After mixing the sodium-based montmorillonite solution and the functional modifier solution prepared in Example 1, adjusting the pH of the mixed solution to 3-5, heating to 70° C., stirring and reacting for 12 hours, and post-treating to obtain modified montmorillonite;
[0064] The sodium-montmorillonite solution is made of sodium-montmorillonite and a mixed solvent; the solution containing a functional modifier is made of a functional modifier and a water / ethanol (water and ethanol have a volume ratio of 1:9) mixed solvent; the mass fraction of sodium-montmorillonite in the sodium-montmorillonite solution is 30%. The mass fraction of the functional modifier in the solution containing a functional modifier is 10%. The mass ratio of the sodium-montmorillonite to the functional modifier is 10:2.
[0065] Example 4
[0066] Preparation of modified montmorillonite:
[0067] After mixing the sodium-based montmorillonite solution and the functional modifier solution prepared in Example 2, adjusting the pH of the mixed solution to 3-5, heating to 80° C., stirring and reacting for 6 hours, and post-treating to obtain modified montmorillonite;
[0068] The sodium-montmorillonite solution is made of sodium-montmorillonite and a mixed solvent; the solution containing a functional modifier is made of a functional modifier and a water / ethanol (water and ethanol have a volume ratio of 2:8) mixed solvent; the mass fraction of sodium-montmorillonite in the sodium-montmorillonite solution is 40%. The mass fraction of the functional modifier in the solution containing a functional modifier is 10%. The mass ratio of the sodium-montmorillonite to the functional modifier is 10:3.
[0069] Example 5
[0070] Preparation of cross-linked resin:
[0071] After 0.12 mol hexamethylene diisocyanate trimer, 0.1 mol alcohol hydroxyl di-terminated silicone oil and 200 mL acetone are uniformly mixed, the mixture is heated to 50°C under nitrogen protection, 10 g of organic tin catalyst (T12) is added under stirring, the mixture is kept warm and stirred for 8 hours, the reaction is stopped, the mixture is rotary evaporated, washed with water, and dried to obtain a cross-linked resin, wherein the average relative molecular weight of the alcohol hydroxyl di-terminated silicone oil is 1500-2000, and the viscosity is 25°C cts 50-100.
[0072] Example 6
[0073] Preparation of cross-linked resin:
[0074] After 0.15 mol hexamethylene diisocyanate trimer, 0.1 mol alcohol hydroxyl di-terminated silicone oil and 200 mL toluene are mixed evenly, heated to 50°C under nitrogen protection, 10 g of organic tin catalyst (T12) is added under stirring, and the reaction time is continued to be kept warm and stirred for 4 hours, the reaction is stopped, rotary evaporated, washed with water, and dried to obtain a cross-linked resin, wherein the average relative molecular weight of the alcohol hydroxyl di-terminated silicone oil is 1500-2000, and the viscosity is 25°C cts 50-100.
[0075] Example 7
[0076] Preparation of high temperature resistant and anti-welding slag cable sheath material:
[0077] 1. Prepare the following raw materials in parts by weight: 80 parts of TPU, 16 parts of modified montmorillonite prepared in Example 3, 35 parts of cross-linked resin prepared in Example 5, 0.1 parts of lubricant (polyethylene wax), 6 parts of co-crosslinking agent (3,5-dimethylthiotoluenediamine), and 0.5 parts of reaction catalyst (triethylenediamine);
[0078] 2. Mix the above raw materials in parts by weight and add a twin-screw extruder, and granulate by extrusion to obtain a sheath material at an extrusion temperature of 190-245°C.
[0079] Example 8
[0080] Preparation of high temperature resistant and anti-welding slag cable sheath material:
[0081] 1. Prepare the following raw materials in parts by weight: 90 parts of TPU, 20 parts of modified montmorillonite prepared in Example 3, 20 parts of cross-linked resin prepared in Example 5, 0.6 parts of lubricant (polyethylene wax), 4 parts of co-crosslinking agent (3,5-dimethylthiotoluenediamine), and 0.2 parts of reaction catalyst (triethylenediamine);
[0082] 2. Mix the above raw materials in parts by weight and add a twin-screw extruder, and granulate by extrusion to obtain a sheath material at an extrusion temperature of 190-245°C.
[0083] Example 9
[0084] Preparation of high temperature resistant and anti-welding slag cable sheath material:
[0085] 1. Prepare the following raw materials in parts by weight: 100 parts of TPU, 32 parts of modified montmorillonite prepared in Example 3, 18 parts of cross-linked resin prepared in Example 5, 0.1-1.5 parts of lubricant (polyethylene wax), 2 parts of co-crosslinking agent (3,5-dimethylthiotoluenediamine), and 0.1 parts of reaction catalyst (triethylenediamine);
[0086] 2. Mix the above raw materials in parts by weight and add a twin-screw extruder, and granulate by extrusion to obtain a sheath material at an extrusion temperature of 190-245°C.
[0087] Comparative Example 1
[0088] Preparation of cable sheath material:
[0089] Compared with Example 8, the auxiliary cross-linking agent in the raw material is deleted, and the rest is the same.
[0090] Comparative Example 2
[0091] Compared with Example 8, the modified montmorillonite in the raw material was replaced with montmorillonite prepared by the following steps, and the rest was the same:
[0092] Preparation of modified montmorillonite:
[0093] After mixing the sodium montmorillonite solution and the polyhydroxylated silane coupling agent solution prepared in step A2 of Example 1, adjusting the pH of the mixed solution to 3-5, heating to 70° C., stirring and reacting for 12 hours, and post-treating to obtain modified montmorillonite;
[0094] The sodium-montmorillonite solution is made of sodium-montmorillonite and a mixed solvent; the solution containing a functional modifier is made of a functional modifier and a water / ethanol (water and ethanol volume ratio is 1:9) mixed solvent; the mass fraction of sodium-montmorillonite in the sodium-montmorillonite solution is 30%. The mass fraction of the polyhydroxylated silane coupling agent in the solution containing a polyhydroxylated silane coupling agent is 10%. The mass ratio of the sodium-montmorillonite to the functional modifier is 10:2.
[0095] Comparative Example 3
[0096] Preparation of cable sheath material:
[0097] Compared with Example 8, the modified montmorillonite in the raw material is deleted, and the rest is the same.
[0098] Comparative Example 4
[0099] Preparation of cable sheath material:
[0100] Compared with Example 8, the modified montmorillonite and the cross-linked resin in the raw materials are deleted, and the rest are the same.
[0101] The sheath materials obtained in Examples 7-9 and Comparative Examples 1-3 were formed and sampled for physical property tests, and the test results are shown in Table 1; wherein, the heat aging resistance test was conducted in accordance with GB / T 7141, and the tensile strength was tested after the heat aging test, and the decrease rate of the tensile strength was calculated; the anti-welding slag point test: an electric iron at 250±20°C was ironed on the sample surface for 3-5s, and it was observed whether there was a focus at the ironing point. If the test showed that there was no focus at the ironing point, the anti-welding slag point test was passed, and if the test showed that there was no focus at the ironing point, the anti-welding slag point test was failed.
[0102] Table 1
[0103]
[0104]
[0105] It can be seen from the data in Table 1 that the sheath materials obtained in Examples 7-9 have good hardness, high temperature resistance and resistance to welding slag spots.
[0106] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0107] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high temperature resistant and anti-welding slag cable sheath material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of TPU, 20-40 parts of modified montmorillonite, 18-35 parts of cross-linking resin, 0.1-1.5 parts of processing auxiliary agent, 2-6 parts of auxiliary cross-linking agent, and 0.1-0.5 parts of reaction catalyst; The cross-linking resin is prepared by mixing and reacting hexamethylene diisocyanate trimer and alcohol hydroxyl double-terminated silicone oil in a molar ratio of 1-1.5:1 in a first organic solvent and in the presence of an organic tin catalyst.
2. The high temperature resistant and anti-welding slag cable sheath material according to claim 1, characterized in that: The reaction temperature of the hexamethylene diisocyanate trimer and the alcohol hydroxyl double-terminated silicone oil is 50-70° C., and the reaction time is 4-8 hours.
3. The high temperature resistant and anti-welding slag cable sheath material according to claim 1, characterized in that: The first organic solvent is one of acetone, tetrahydrofuran, benzene and toluene.
4. The high temperature resistant and anti-welding slag cable sheath material according to claim 1, characterized in that: The preparation reaction of the modified montmorillonite comprises: After mixing the sodium-based montmorillonite solution and the solution containing the functional modifier, the pH of the mixed solution is adjusted to 3-5, heated to 70-80°C, stirred for reaction for 6-12 hours, and post-treated to obtain modified montmorillonite; Wherein, the sodium-montmorillonite solution is made of sodium-montmorillonite and a first mixed solvent; the solution containing a functional modifier is made of a functional modifier and a first mixed solvent; and the first mixed solvent is formed by mixing water and ethanol.
5. The high temperature resistant and anti-welding slag cable sheath material according to claim 4, characterized in that: The functional modifier is prepared by reacting chlorinated hydroxybenzophenone and a polyhydroxylated silane coupling agent in a second organic solvent; The polyhydroxylated silane coupling agent is prepared by reacting 3-chloropropyltrimethoxysilane and polyol in a third organic solvent.
6. The high temperature resistant and welding slag proof cable sheath material according to claim 5, characterized in that: The reaction temperature of the chlorinated hydroxybenzophenone and the polyhydroxylated silane coupling agent is 20-60° C., and the reaction time is 2-5 hours.
7. The high temperature resistant and welding slag proof cable sheath material according to claim 5, characterized in that: The molar ratio of the chlorinated hydroxybenzophenone to the polyhydroxylated silane coupling agent is 1:1; and the second organic solvent is one of dichloromethane, tetrahydrofuran, benzene and toluene.
8. The high temperature resistant and welding slag proof cable sheath material according to claim 5, characterized in that: The molar ratio of the 3-chloropropyltrimethoxysilane to the polyol is 1:1-1.5; the reaction temperature of the 3-chloropropyltrimethoxysilane and the polyol is 60-65°C, and the reaction time is 2-7h; the polyol is one of glycerol and pentaerythritol; and the third organic solvent is one of ethyl acetate, tetrahydrofuran, benzene and toluene.
9. The high temperature resistant and welding slag proof cable sheath material according to claim 5, characterized in that: The chlorinated hydroxybenzophenone is prepared by reacting chloroacetyl chloride and 2,4-dihydroxybenzophenone in a fourth organic solvent.
10. The high temperature resistant and welding slag proof cable sheath material according to claim 9, characterized in that: The molar ratio of the chloroacetyl chloride to 2,4-dihydroxybenzophenone is 1:1, and the fourth organic solvent is one of dichloromethane, tetrahydrofuran, benzene, and toluene; the reaction temperature of the chloroacetyl chloride and 2,4-dihydroxybenzophenone is 0-30° C., and the reaction time is 2-7 hours.
Citation Information
Patent Citations
Polyurethane adhesive containing modified montmorillonite and preparation method thereof
CN108485585A
Regenerated modified plastic based on waste plastic
CN114479429A
High-flame-retardant polyurethane cable protection composite material and preparation method thereof
CN115716984A
Wear-resistant and aging-resistant modified polyurethane elastomer composite material as well as preparation method and application thereof
CN116606542A
Material for toe-protecting intelligent elastomer toes of safety shoes and preparation method of material
CN116656117A
Cited By
High-temperature-resistant and torsion-resistant cable
CN119708818A
A high temperature resistant and twist resistant cable
CN119708818B
Lightweight ultralow-temperature-resistant flexible reel cable
CN121171701A
Lightweight ultra-low temperature resistant flexible reel cable
CN121171701B